ANALISIS MENGENAI KEDUDUKAN PERJANJIAN NOMINEE ANTARA KARPIKA WATI (WNI) DAN ALAIN MAURICE PONS (WNA) (CONTOH PUTUSAN NOMOR 3403 K/PDT/2016) - Inka Cyntiya Sulastin; Stanislaus Atalim (Jurnal Hukum Adigama, 2019)
Nominee agreements in terms of land ownership between Indonesian citizens and foreign nationals according to Positive Law in Indonesia are prohibited and not valid, but at present there are many foreign citizens who come to Indonesia with various purposes, one of which is to build a business, business, until investment in a way outside the applicable regulations. One way for foreign citizens to have land rights in Indonesia is by marrying Indonesian citizens and / or utilizing local indigenous people by borrowing the names of Indonesian citizens who can have land rights to bind themselves to each other in the terms of the nominee agreement. The problem that the author examines in this case is how the position of the nominee agreement in land ownership according to the positive legal system in Indonesia that occurred in the case between Karpika Wati (an Indonesian citizen) and Alain Maurice Pons (a foreign citizen) in accordance with decision No. 3403 K / PDT / 2016 The author conducts research using the normative method that will use the relevant laws to conduct a review of the problem. It can be concluded that the position of the nominee agreement in the case between Karpika Wati and Alain Maurice Pons violates the provisions of positive law in force in Indonesia, violates the provisions of the Civil Code, the Basic Agrarian Law, and the Marriage Law.